The Relevance of Islamic Education Theory in the 2nd Century Hijriyah in the Development of Contemporary Education - Mardani, Dadan; Maulani, Hikmah; Saleh, Nalahuddin; Hezam, Motea Naji Dabwan; Bustomi, Jenal; Ruhendi, Ateng; Yunus, Badruzzaman M. (INCARE, International Journal of Educational Resources, 2025)
Islamic education in the 2nd century Hijriyah played a crucial role in shaping the sustainable Islamic educational system that continues to this day. During this period, prominent Muslim scholars such as Abu Hanifah, Malik bin Anas, and Al-Shafi’i formulated educational concepts based on the Qur'an and Sunnah, which later developed in educational institutions such as halaqah and early madrasas. This study aims to analyze the relevance of Islamic educational theories from the 2nd century Hijriyah in the development of contemporary education systems. Using a qualitative approach based on literature studies, this research examines the educational principles applied in that era and their contributions to modern learning systems. The findings indicate that key principles, such as value-based education, interactive discussion methods, and the integration of religious and secular sciences, remain relevant to contemporary educational challenges. This article contributes by linking the history of Islamic educational thought with the demands of a more holistic and value-based modern education system.